2021
DOI: 10.3390/biomedicines9101419
|View full text |Cite
|
Sign up to set email alerts
|

Initial Biological Assessment of Upconversion Nanohybrids

Abstract: Nanoparticles for medical use should be non-cytotoxic and free of bacterial contamination. Upconversion nanoparticles (UCNPs) coated with cucurbit[7]uril (CB[7]) made by combining UCNPs free of oleic acid, here termed bare UCNPs (UCn), and CB[7], i.e., UC@CB[7] nanohybrids, could be used as photoactive inorganic-organic hybrid scaffolds for biological applications. UCNPs, in general, are not considered to be highly toxic materials, but the release of fluorides and lanthanides upon their dissolution may cause c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Qi et al observed the cell morphology by transmission electron microscopy (TEM), and the results indicated that MNPs exhibited the ability to promote the expression of Bax, which is a programmed cell death acceleration protein, and induced greater cell necrosis as well. Moreover, UCNPs are not considered toxic materials in general, and the release of fluorides and lanthanides during the dissolution process of UCNPs may introduce cytotoxicity …”
Section: Potential Health Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Qi et al observed the cell morphology by transmission electron microscopy (TEM), and the results indicated that MNPs exhibited the ability to promote the expression of Bax, which is a programmed cell death acceleration protein, and induced greater cell necrosis as well. Moreover, UCNPs are not considered toxic materials in general, and the release of fluorides and lanthanides during the dissolution process of UCNPs may introduce cytotoxicity …”
Section: Potential Health Risksmentioning
confidence: 99%
“…Moreover, UCNPs are not considered toxic materials in general, and the release of fluorides and lanthanides during the dissolution process of UCNPs may introduce cytotoxicity. 135 Metal nanoparticles, especially precious metal nanoparticles such as gold and silver, are a commonly used nanomaterials in the food and medical fields. However, in recent years, research studies have focused on AuNPs exposure in a skin penetration route.…”
Section: Materials In the Elimination Of Food Hazardsmentioning
confidence: 99%
“…[80] UCNPs display exceptional optical properties, such as multiple and narrow emission bands, non-photobleaching, nonphotoblinking, long luminescence lifetimes, high stability and low cytotoxicity. [81][82][83] Especially, the use of NIR excitation light has attracted the attention of researchers during the last decade due to its high penetration depth in tissues, as well as low background autofluorescence in biosamples. [84] Hence, UCNPs have been used for different widespread applications such as in bioimaging, phototherapy or biosensing, but also in anticounterfeiting, solar cells, or photocatalysis.…”
Section: Chiroptical Response In Upconversion Nanoparticlesmentioning
confidence: 99%
“…The cytotoxic effect of UCNPs has been found to vary based on surface coating: bare UCNPs resulted in elevated cytotoxicity when compared with silica‐ or cucurbit[7]uril‐ coated UCNPs, and cell line: HeLa and RAW 264.7 cells exhibited elevated cytotoxicity whereas EAhy 926 endothelial cells did not. [ 179 ] Additionally, neither 980 nm nor 808 nm lasers with power densities of 2.5 W cm −2 for as long as 20 min caused a notable reduction in HeLa cell viability. However, at these levels, a nonsignificant downward trend between the controls, 10, and 20 min time points may point to reaching an upper threshold of laser power for this experiment.…”
Section: Bioimaging In Live Cellsmentioning
confidence: 99%